Banyuwangi English Dormitory as a Source of Learning Local History and Culture - Ayu Oktaviyani; Intan Nur Aini; Ahmad Ali Munazat (SINGOSARI, 2026)
This study aims to uncover the historical and cultural value of Asrama Inggrisan Banyuwangi and explore its potential as a source of learning about local history. As one of the Dutch colonial heritage buildings on the eastern tip of Java Island, Asrama Inggrisan has an important role in the history of civilization and social interaction in the Banyuwangi region. This building still holds a hidden narrative that documents the socio-cultural transformation and cultural heritage of the area. We aim to explore the narrative embedded in Asrama Inggrisan and its education as a marker of local historical and cultural identity and how this narrative can strengthen historical awareness and act as an educational heritage tourism destination. The research was conducted using a historical method that includes the stages of heuristics, verification, interpretation, and historiography. In addition, an interdisciplinary approach was used by integrating historical studies, cultural anthropology, and history education to examine the educational and cultural values ​​of this site. The results of the study show that Asrama Inggrisan is not only a physical heritage from the colonial era, but also a space that records social dynamics and cultural acculturation. Building awareness of local heritage sites, with the right preservation strategy, Asrama Inggrisan can be optimized as a medium for learning local history as well as a cultural tourism attraction that supports economic and cultural development in Banyuwangi. Utilizing this site as a source for learning local history can strengthen the historical awareness of the younger generation and support the preservation of local culture. This study suggests the development of contextual learning programs using local historical sites such as Asrama Inggrisan to teach integrated history as a preservation of local culture and support the preservation of history education.